New Directions in Antithrombotic Therapy - Helwick, Caroline (MD Conference Express, 2007)
This article discusses strategies for long-term antithrombotic therapy, ways to balance the risks and benefits of antithrombotic therapy, as well as gives an overview of evidence supporting the use of long-term antithrombotic therapy after acute coronary syndrome, and suggests strategies for balancing the benefits and risks of long-term antithrombotic therapy for patients with NSTEMI or STEMI.